The Neuroprotective and Therapeutic Effects of Medicinal Plants and Natural Products against Aluminium Chloride-Induced Alzheimer's Disease: Recent Update - Ojetunde, Ayodeji Oluwatobi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Alzheimer's disease currently affects more than 35 million individuals worldwide. Aluminium has been implicated in the pathogenesis of various cognitive disorders. Meanwhile, aluminium chloride (AlCl3) has a significant impact on the progression of neurodegenerative diseases including Alzheimer's disease. The majority of Alzheimer's disease medications now on the market are cholinesterase inhibitors. However, the effectiveness of these drugs is limited because they can't totally arrest the progression of the disease. The utilization of medicinal plants and natural products may present excellent prospective options for Alzheimer's disease prevention and therapy. This study summarized medicinal plants and natural products for the prevention and treatment of AlCl3-induced Alzheimer's disease as an alternative therapy using published data in the literature from the years 2021-2023. The medicinal plants and natural products help to reduce Alzheimer's disease pathogenesis by controlling different pathways and could be used as a therapeutic agent against the symptoms. The majority of the medicinal plants and natural products discussed in this review have been shown to have neuroprotective, antioxidant, anti-amyloid, anti-inflammatory, anticholinesterase, anti-apoptotic, and therapeutic actions. Therefore, medicinal plants and natural products may offer neuroprotective and therapeutic effects in the treatment of Alzheimer's disease.